Personal genomic passport: health benefits and ethical risks - Moskalov, Vitalii; Kadenko, Iryna; Dekhtiariova, Olena (My University, 2024)
The article highlights the achievements of modern molecular biology, which are the basis of the concept of genomic passporting. Areas of use of this tool in health care, medicine and education are discussed. It was considered advantages of this toolkit in groups of children and adolescents. A discussion and risk assessment of the implementation of genomic passports was conducted. У статті висвітлені досягнення сучасної молекулярної біології, що лежать в основі концепції геномної паспортизації. Обговорені напрями використання цього інструменту в здоров’язбереженні, медицині та освіті. Розглянуті переваги цього інструментарію у групах дітей та підлітків. Проведено обговорення та оцінку ризиків від впровадження геномних паспортів.
Moskalov V. Personal genomic passport: health benefits and ethical risks / Vitalii Moskalov, Iryna Kadenko, Olena Dekhtiariova // Безпека життєдіяльності, екологія і охорона здоров’я дітей і молоді ХХІ сторіччя: сучасний стан, проблеми та перспективи : зб. праць ХІV Міжнар. наук-практ. конф. – Переяслав, 2024. – Вип. 14. – С. 9–11.
Keywords: особистий геномний паспорт, секвенування нового покоління, етичні ризики; personal genomic passport, next-generation sequencing, ethical risks